Dependable software engineering : theories, tools, and applications : 5th International Symposium, SETTA 2019, Shanghai, China, November 27-29, 2019, Proceedings /: theories, tools, and applications : 5th International Symposium, SETTA 2019, Shanghai, China, November 27-29, 2019, Proceedings. (2019) - Unknown
No abstract available